Nanobodies raised against monomeric ɑ-synuclein inhibit fibril formation and destabilize toxic oligomeric species - Iljina, Marija (BMC Biol, 2017)
BACKGROUND: The aggregation of the protein ɑ-synuclein (ɑS) underlies a range of increasingly common neurodegenerative disorders including Parkinson’s disease. One widely explored therapeutic strategy for these conditions is the use of antibodies to target aggregated ɑS, although a detailed molecular-level mechanism of the action of such species remains elusive. Here, we characterize ɑS aggregation in vitro in the presence of two ɑS-specific single-domain antibodies (nanobodies), NbSyn2 and NbSyn87, which bind to the highly accessible C-terminal region of ɑS. RESULTS: We show that both nanobodies inhibit the formation of ɑS fibrils. Furthermore, using single-molecule fluorescence techniques, we demonstrate that nanobody binding promotes a rapid conformational conversion from more stable oligomers to less stable oligomers of ɑS, leading to a dramatic reduction in oligomer-induced cellular toxicity. CONCLUSIONS: The results indicate a novel mechanism by which diseases associated with protein aggregation can be inhibited, and suggest that NbSyn2 and NbSyn87 could have significant therapeutic potential. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-017-0390-6) contains supplementary material, which is available to authorized users.